2011
DOI: 10.1016/j.jcrs.2010.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Combined penetrating keratoplasty and implantation of iris prosthesis intraocular lenses after ocular trauma

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Moreover, the three-point Z-suture fixation technique offers the advantages of a knotless approach. Although difficulties with centration of other types of iris prosthesis have been described in the literature, the artificial iris complex remained well centered in all eyes in our series [8]. Thus, the three-point fixation allows a wellcentered artificial iris-IOL complex and seems to be sufficient.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the three-point Z-suture fixation technique offers the advantages of a knotless approach. Although difficulties with centration of other types of iris prosthesis have been described in the literature, the artificial iris complex remained well centered in all eyes in our series [8]. Thus, the three-point fixation allows a wellcentered artificial iris-IOL complex and seems to be sufficient.…”
Section: Discussionmentioning
confidence: 59%
“…Aside from esthetic aspects, partial or total loss of iris tissue may also be related to various degrees of glare, photophobia, and visual impairment. In patients with major iris defects, an artificial iris prosthesis provides satisfactory anterior segment reconstruction with a remarkable functional outcome (3)(4)(5)(6)(7)(8)(9)(10) . Various implants have been developed for the treatment of aphakia with aniridia.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported on effective and safe surgical intervention with Morcher black-diaphragm IOL (Morcher 67F BDI, Morcher GmBH, Stuttgart, Germany) for the treatment of both total or partial aniridia in aphakic cases (6,7) . The Ophtec iris reconstruction lens with the color options of brown, blue, and green (Ophtec USA, Boca Raton, FL, USA) has also been reported to provide better cosmetic outcomes as well as remarkable visual improvement (8,9) . In cases with partial iris defects, intraocular implantation of the Artisan iris reconstruction implant (Ophtec, Groningen, The Netherlands) may be chosen for cosmetic and functional improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Iris implants have been available since 1991 and many studies have shown their efficacy to resolve the visual symptoms associated with iris defects [1][2][3][4][5][6]. However, most implant models have substantial limitations; in particular most require large incisions for implantation and do not restore the original appearance of the iris.…”
Section: Introductionmentioning
confidence: 99%